2017
DOI: 10.1371/journal.pone.0188183
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of open-source software for DNA mixture interpretation based on a quantitative continuous model

Abstract: In criminal investigations, forensic scientists need to evaluate DNA mixtures. The estimation of the number of contributors and evaluation of the contribution of a person of interest (POI) from these samples are challenging. In this study, we developed a new open-source software “Kongoh” for interpreting DNA mixture based on a quantitative continuous model. The model uses quantitative information of peak heights in the DNA profile and considers the effect of artifacts and allelic drop-out. By using this softwa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
25
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(28 citation statements)
references
References 28 publications
3
25
0
Order By: Relevance
“…These include the New York City Office of Chief Medical Examiner's FST Tool [3], TrueAllele® [4], and STRmix™ [5]. More recently the validation of GenoProof Mixture 3 [6] and Kongoh [7] has been reported.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…These include the New York City Office of Chief Medical Examiner's FST Tool [3], TrueAllele® [4], and STRmix™ [5]. More recently the validation of GenoProof Mixture 3 [6] and Kongoh [7] has been reported.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…It has also been demonstrated that factors such as PCR and the content of allele frequency databases have an impact on the variation in the LR computed using a continuous method [ 28 , 29 ]. Recent work has demonstrated that differences in output between semi-continuous and continuous systems result in clear differences in the LRs for some samples [ 10 , 30 , 31 ]. Despite these studies, comparisons between continuous probabilistic systems are not readily available in the literature, though some examples using small datasets do exist.…”
Section: Introductionmentioning
confidence: 99%
“…Despite these studies, comparisons between continuous probabilistic systems are not readily available in the literature, though some examples using small datasets do exist. For example, Morimoto et al [ 31 ] compare the continuous system Kongoh to another continuous system, EuroForMix, and demonstrate that for most high-template simple mixtures tested the LR outcomes were similar; however differences in LRs obtained from each model were obtained for more complex mixtures wherein the authors attributed the variation in outputs as “differences in the computational principle of estimating peak height variances”. Though reports of inter-model comparisons in the scientific literature do exist, sometimes resulting in the use of multiple softwares to test one item of evidence [ 30 ], the published work use limited datasets or do not replicate the runs; thus, in this work, and pursuant to PCAST’s recommendation to publish large-scale studies, we supplement the forensic and scientific literary record by examining the variability between results obtained from four variants of CEESIt [ 32 ], a tool that computes a continuous LR for a person of interest.…”
Section: Introductionmentioning
confidence: 99%
“…The use of MCMC is not novel and has been used to solve many complex problems within chemistry, physics, biology, statistics, and computer science. The continuous model software Kongoh utilizes MLE. Other continuous solutions of which we are aware include LikeLTD‐ht , DNAmixtures , and EuroForMix .…”
Section: Introduction To Probabilistic Genotypingmentioning
confidence: 99%